1979
DOI: 10.1136/jcp.32.8.802
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical demonstration of J chain: a marker of B-cell malignancy.

Abstract: Many B-cell lymphomas can be shown to contain cytoplasmic immunoglobulin which is characteristically monotypic with respect to light chains. In Hodgkin's disease, however, the Reed-Sternberg cells have been shown to contain both immunoglobulin light chains. This finding, which is also present in some other lymphomas, has been used as evidence both for and against a B-cell derivation of these cells. J chain is present in normal immunoblasts irrespective of the class of immunoglobulin being synthesised and, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0
1

Year Published

1980
1980
1987
1987

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 17 publications
1
10
0
1
Order By: Relevance
“…This finding, obtained on serial sections from 15 cases of nodular paragranuloma, was confirmed by double immunostaining of one case of nodular paragranuloma for x and A using a modification of the sequential double staining method of Nakane (1968). Furthermore, Poppema (1980 reported that L-and H-type H and SR cells contain J chains, a proven marker for non-malignant and malignant B-cells (Brandtzaeg, 1974;Brandtzaeg and Berdal, 1975;Isaacson, 1979;Stein et al, 1980), in contrast to typical H and SR cells and lacunar type H and SR cells, which are devoid of J chains (Isaacson, 1979). From all these findings, Poppema and co-workers (1979a,b;Poppema, 1980) concluded that L-and H-type and SR cells of nodular pragranuloma produce Ig, rather than taking it up from the environment, and are hence a special type of H and SR cells (differing from both typical and lacunar type H and SR cells) possibly derived from certain B immunoblasts.…”
Section: Discussionmentioning
confidence: 98%
“…This finding, obtained on serial sections from 15 cases of nodular paragranuloma, was confirmed by double immunostaining of one case of nodular paragranuloma for x and A using a modification of the sequential double staining method of Nakane (1968). Furthermore, Poppema (1980 reported that L-and H-type H and SR cells contain J chains, a proven marker for non-malignant and malignant B-cells (Brandtzaeg, 1974;Brandtzaeg and Berdal, 1975;Isaacson, 1979;Stein et al, 1980), in contrast to typical H and SR cells and lacunar type H and SR cells, which are devoid of J chains (Isaacson, 1979). From all these findings, Poppema and co-workers (1979a,b;Poppema, 1980) concluded that L-and H-type and SR cells of nodular pragranuloma produce Ig, rather than taking it up from the environment, and are hence a special type of H and SR cells (differing from both typical and lacunar type H and SR cells) possibly derived from certain B immunoblasts.…”
Section: Discussionmentioning
confidence: 98%
“…It has been established by our recent studies (13, 14) that intranuclear spots of J chain, invisible without immunostaining, are nucleolus associated, and that this phenomenon is not infrequently encountered in myeloma cells. Little is so far known of the clinical significance of J chain in the hematological field except for the observation that the cytoplasmic J chain is a useful marker for B-cell malignancies (9)(10)(11). It seems likely that the increased levels of J chain seen in monomeric Ig-secreting myeloma cells are a function of their neoplastic state (4).…”
Section: Discussionmentioning
confidence: 99%
“…8 Sequential sections ofMTL stained with anti-a-antiserum at (a) I111000 (b) and I11100. The abnormal a-chain in the plasma cells is best stained with the more concentrated antiserum (compare Fig.…”
Section: Discussionmentioning
confidence: 99%